PERBEDAAN KEBOCORAN TEPI RESTORASI OPEN â SANDWICH KAVITAS KELAS V MENGGUNAKAN RESIN KOMPOSIT DENGAN SEMEN IONOMER KACA KONVENSIONAL, SEMEN IONOMER KACA MODIFIKASI RESIN DAN KOMPOMER SEBAGAI LAPISAN PENGGANTI DENTIN - , DIANSARI WIRYO, drg. Ema Mulyawati, MS., Sp.KG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Marginal leakage is often become the failure factor of cavity class V restorations. Sandwich technique is one of restoration techniques that can be used to minimized marginal leakage. Open sandwich technique is used to restore class V cavity of which gingival wall had reached cemento enamel junction. This study aims to compare the leakage of open sandwich class V restoration using conventional glass ionomer cement, resin modified glass ionomer cement and compomer as replacement layer of dentine. Eighteen premolars were used as samples of this study, 5x3x2 mm cavities were prepared on buccal and lingual side of each tooth. Samples were divided into 3 groups, each group was restorated by open â sandwich technique. Group I used composite resin and conventional glass ionomer cement, group II used composite resin and resin modified glass ionomer cement, group III used composite resin and compomer. Specimens were stored in artificial saliva pH 6,8 in 37 o C for 24 hours, and then thermocycled 150 times at 12 o C + 2 and 60 o C+2, 1 minute in each temperature. Samples were immersed in 2% methylene blue dye for 24 hours, then samples were cut in the middle buccal â lingually. The penetration of blue methylene solution in samples were observed with stereomicroscope magnifying 10x. Statistic result of this study showed no differences in marginal leakage of open sandwich restoration on class V cavities in three groups.